Radiosensitization effect by HDAC inhibition improves NKG2D-dependent natural killer cytotoxicity in hepatocellular carcinoma - Liu, Yu-Fan; Chiang, Yun; Hsu, Feng-Ming; Tsai, Chiao-Ling; Cheng, Jason Chia-Hsien (Frontiers in Oncology, 2022)
Background: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related death worldwide. Radiotherapy (RT) controls HCC unsatisfactorily and temporarily. Histone deacetylase inhibitor (HDACi) is a heterogeneous group of epigenetic therapeutics with promising anticancer effects and synergism in combination with RT. HDACi modulates natural killer (NK) cell ligand expression on tumor cells, and leads to immune evasion of cancer cells. Expressions of NK group 2D (NKG2D) ligands on cancer cells determine the cytotoxic effect by interacting with NKG2D receptor on NK cells. However, the role of NKG2D signaling in HCC upon combined RT and HDACi remains unclear. Method: In vitro co-culture system with NK cells was tested for human and murine HCC cell lines. Pan-HDACi (panobinostat) and specific HDAC4 knockdown (HDAC4-KD) were used for HDAC inhibition. Clonogenic assay and flow cytometry examined HCC cell survival and NKG2D ligand expression, respectively. Syngeneic mouse model was used to validate the radiosensitizing effect in vivo. Results: Combined RT and HDACi/HDAC4-KD significantly enhanced NK cell-related cytotoxicity and increased NKG2D ligands, MICA/MICB expressions in human and RAE-1/H60 expressions in murine HCC cells. Delayed tumor growth in vivo by the combinational treatment of RT and HDACi/HDAC4-KD was shown with the associated NKG2D ligand expressions. However, NKG2D receptor did not significantly change among tumors. Conclusion: Radiosensitizing effect with combined RT and HDAC inhibition increased the expression of NKG2D ligands in HCC cells and enhanced their susceptibility to NK cell-mediated cytotoxicity. These findings imply the potential use of combined RT/HDACi and NK cell-directed immunotherapy.